Meningkatkan Motivasi Dalam Menjaga Kesehatan Gigi Mulut Melalui Pendidikan Kesehatan - Mirawati Hamid, Ellis; Thioritz, Ernie; Fiqhi, Nur (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Oral health education is important in maintaining general health, especially in children and adolescents who are vulnerable to these problems. Lack of awareness and behavior in caring for oral health is the main risk factor. Methods such as dental and oral health education through the WhatsApp application are very necessary to increase understanding and behavior in caring for dental and oral health. The aim of this research is to determine the level of motivation of students at SMAN 1 Barru before and after being given counseling regarding oral health education using poster media via the WhatsApp application. This research is a type of quantitative research which has a sample size of 70 people with a sampling technique, namely stratified random sampling. The data analysis used was univariate & bivariate analysis with a statistical test, namely the Paired T Test. The results of the research showed that providing counseling using poster media via the WhatsApp application was relatively effective in increasing the motivation of students at SMA Negeri 1 Barru in maintaining healthy teeth and mouth.